Tropical forest root characteristics and responses to drying across environmental gradients - Longhi Cordeiro, Amanda, author; Cusack, Daniela F., advisor; Ojima, Dennis, committee member; Cotrufo, M. Francesca, committee member; Conant, Richard, committee member (Colorado State University. Libraries, 2024)
Fine roots represent the interface between plants and soils, and as such regulate all major biogeochemical cycles in terrestrial ecosystems, including tropical forests. Tropical forests play a crucial role in global carbon (C) cycling, largely due to their extensive root biomass and significant soil C stocks. However, these ecosystems have been experiencing more frequent severe droughts across some regions and are predicted to continue experiencing these extreme drought events in the future. This dissertation seeks to contribute to the understanding and synthesis of tropical root responses to drying in varying environmental conditions. In chapter 1, I gave an introduction about the importance of fine roots to ecosystem function and the impacts of drying in tropical forests. In chapter 2, I characterized root biomass, morphology, nutrient content, colonization to 1.2 meters depth as well as and arbuscular mycorrhizal fungal (AMF) to 20 cm depth in 32 plots across four distinct lowland Panamanian forests which are representative of the vast variation in soil fertility and mean annual precipitation (MAP) found across tropical forests. Root characteristics measurements, such as morphology and chemistry, at soil layers deeper than 30 cm have been rarely documented and to the best of knowledge this is the first study in tropical forests. I observed that that some root traits changed with soil depth similarly across sites while others had site-specific variation. I also observed larger variation at the soil surface and that morphological traits, in addition to root biomass can affect soil C stocks. In chapter 3, the effects of experimental and seasonal drying on fine root dynamics were explored using a partial throughfall reduction experiment across the same 32 plots as in chapter 2. I found that chronic drying impacted root biomass, productivity, morphology and arbuscular mycorrhizal fungi (AMF) colonization. Root biomass and characteristics also changed across seasons with different dynamics across depths. Chapter 4 focused on the effects of drought on tropical seedling development in a controlled chamber environment. I observed that drying decreased seedling growth, but high soil fertility and AMF inoculation mitigated these effects. I also observed changes in root morphology, leached C, new C allocation patterns, and aboveground traits in response to drought, but with usually interacting effects with fertility and AMF inoculation. Chapter 5 contributes a tropical root database (TropiRoot 1.0 database) with root data extracted from scientific papers across different countries and continents. Overall, this dissertation provides novel results and insights into the variation in root characteristics among tropical forests and their responses to climatic drying with interacting effects of fertility, symbionts and soil depth effects. It brings novel measurements that have never been published in tropical forest studies. In chapter 2, I found novel results about how different tropical forests had similar patterns of root variation with depth. It indicated differences in resources acquisition at the soil surface (likely for nutrients) and at deeper soil layers (likely for water) that are usually less investigated. I also showed a large variation of roots at surface soil across different forests that may influence forest responses to global change factors. In chapter 3, I supported some results across the literature such as drying decreasing root growth at the soil surface. However, I added new results such as drying decreasing root productivity at deeper soil layers, and changing root morphology and associations with symbionts probably to compensate the lower root growth. All together I observed that drying promoted changes in acquisition strategies and also that fertile forests may respond differently to drying. In chapter 4, I showed some clear tradeoffs in plant traits providing evidence that they are constantly changing in response to the environment. Also, I provided some novel results on the mechanisms, such as nutrient retention, on how mycorrhizal and fertility mitigated some negative effects of drying on plant growth. This aligns with the field study showing some possible resilience in the fertile forests to drying. The findings highlight the complex interactions between root traits and environmental conditions, offering important implications for predicting tropical forest responses to changing moisture and nutrient availability. All these chapters together provided a good understanding on how different forests respond to environmental changes. These impacts on soil C storage, links with root function and possible larger vulnerability of some forests are great topics for future studies.
Zip file contains Appendix 1-3 spreadsheets and Appendix 4 CSV.
Keywords: drought; root; tropical; forest; carbon; trait